Molecular detection of whitefly-transmissible geminiviruses (family Geminiviridae, genus Begomovirus) in the Philippines - Bela-ong, Dennis B. (Animo Repository, 2007)
Whitefly-transmissible geminiviruses (family Geminiviridae, genus Begomovirus) were detected by the polymerase chain reaction (PCR) in total nucleic acid preparations of tomato and squash leaf samples from different areas in the country. Begomovirus DNA fragments were detected by PCR using 3 sets of degenerate primers that amplify different regions of the genomic A DNA component of begomoviruses. The core coat protein primer pair gave the diagnostic ~560 bp amplicons; the top half primers produced ~1.6 kb PCR products; and the bottom half primers yielded ~1.2 kb amplicons. Not all samples produced amplicons of the expected sizes in PCR. Some samples produced bands in all 3 primer sets, some in only 2 of the 3 sets of primers, while some produced PCR fragments in only 1 of the 3 primer pairs, which suggests variation in the virus DNA sequence in terms of the presence or absence of primer annealing sites. Southern blot analysis using as probe the PCR product amplified from a top half clone of the genomic A DNA component of the Philippine isolate of Tomato leaf curl geminivirus (ToLCV- Ph), confirmed the Begomovirus identity of the top half primer pair-generated amplicons. Results confirmed that begomoviruses are responsible for some tomato and squash leaf curl diseases and the prevalence of these diseases threatens sustainable production of tomato and squash in the country.